Studi Pengaruh Literasi Keuangan terhadap Perilaku Konsumtif Mahasiswa - Abidin, Ali Zainal; Pradipta Montoya Putra Pratama, Kenny; Lintang Kumarabuya, Apta; Fadli Rosihan Nuha4, Auziqna (Benefit: Jurnal Manajemen dan Bisnis, 2025)
This study aims to uncover how financial literacy impacts the consumption behavior patterns of university students. This research is essential because financial literacy has become a crucial form of education in today's consumptive era, especially for students. Currently, students are exposed to a plethora of information on social media, including information about product discounts and attractive products that become part of their daily consumption. Through sound financial literacy, students are expected to become more aware and cautious in making financial decisions, particularly in their consumption behavior. This research employs a qualitative research method with case study analysis. The data used are primary and secondary. Primary data were obtained through questionnaires from student respondents, while secondary data were derived from literature studies on student financial literacy and consumptive behavior. The respondents were selected randomly (random sampling) to observe the variation of patterns in the field. The data analysis method used is content analysis, with data validation through source and method triangulation. The results of this study can serve as a basis for related institutions to prioritize financial literacy education for students.